Analisis Teologis Matius 20:20-28 dan Implikasinya bagi Paradigma Hierarki dalam Kepemimpinan Kristen - Asep Afaradi (Sekolah Tinggi Teologi Berita Hidup, 2026)
This study departs from the reality that the concept of hierarchy remains the dominant pattern in various Christian organizations but is often understood within a framework of structural power that is not in harmony with Jesus' teachings on leadership in the Gospels. Matthew 20:20-28 presents a theological perspective that challenges conventional understandings of authority, greatness, and leadership through a redefinition of values in the Kingdom of God. Therefore, this study aims to theologically analyze the text of Matthew 20:20-28 and formulate its implications for the hierarchical paradigm in contemporary Christian leadership. The study uses a descriptive qualitative approach with a theological-exegetical analysis method that includes a study of the literary context of the Gospel of Matthew, a historical-social analysis of the first-century Mediterranean world, and a linguistic analysis of the Koine Greek text, particularly the terms ????????, ??????, and ??????????. Data was obtained through a literature study of the Bible as the primary source and academic literature as the secondary source, then analyzed interpretively and critically in dialogue with modern Christian leadership theory. The results of the study show that Jesus did not abolish the leadership structure but rather transformed the meaning of hierarchy from domination of power to responsibility for service. Greatness in the community of faith is determined by humility, devotion, and self-sacrifice rooted in the example of Christ as the Son of Man who came to serve. This study concludes that hierarchy in Christian leadership needs to be understood as a structure undergoing theological transformation, in which authority functions as a means of community service, not an instrument of domination, thus offering a conceptual contribution to the reconstruction of a more relational and Christological paradigm of church leadership.